The Effect of Probiotic Cellulolytic B-6 Bacteria in Drinking Water On Weight and Physical Quality of Egg In Lohmann Brown Laying Hens Aged 40-48 Weeks - O, Dinda Dwi; Bidura, I G. N. G.; Candrawati, D. P. M. A. (Jurnal Peternakan Tropika; Vol 6 No 3 (2018), 2018)
The purpose of this study was to assess the ability of 0.2% and 0.4% of cellulolytic bacteria B-6 as a probiotic source to increase egg weight and physical quality of egg in Lohmann Brown laying hens aged 40-48 weeks. Hens used in the research is laying hens Lohmann Brown aged 40 weeks as many as 36 heads with homogeneous body weight. The design used in this study was Completely Randomized Design (RAL) with three treatments, namely the provision of drinking water with out the addition of cellulolitik B-6 bacteria as control (A), drinking water with the addition of 0.2% cellulolitik B- 6 bacteria (B), and drinking water with the addition of 0.4% cellulolitik B-6 bacteria (C). Each treatment consisted of six replications and each replicate using of two hens. The variables observed were egg weight, percentage of egg whites, percentage of egg yolk, and percentage of egg shell. The results showed that in laying hens treatment  B and C were egg weight, percentage of egg yolk, and percentage of egg shell significantly defferent (P<0.05) higher than laying hens treatment A, while laying hens treatment B and C percentage of egg white significantly defferent (P<0,05) more low compared to laying hens that get treatment A. It was conclude that giving 0.2% and 0.4% probiotics Cellulolitik B-6 in drinking water can increase egg weight, egg yolk percentage, eggshell percentage, while the percentage of egg whites decreased. Keywords: egg yolk weight, probiotics, cellulolytic bacteria, lohmann brown